'Literal Meaning' or 'Correct ʿaqīda'? The Reflection of Theological Controversy in Indonesian Qur'an Translations. Issue 3 (October 2015) - Pink, Johanna
Abstract: This paper deals with the traces of theological controversies in translations of the Qur'an into Bahasa Indonesia. It examines thirteen translations that have been published between the 1920s and the present time, discusses problems in the study of these sources, and analyses the exegetical choices made by the translators based on a number of case studies. These include Qur'anic verses that touch upon the issue of free will versus predestination, the relationship between God and Man, and the anthropomorphic attributes of God. The decisions that translators make have to take into account a number of factors such as discrepancies between the source language and the target language, the wish to remove ambiguities, or inconsistencies between the source text and external structures – for example, theological dogma or ḥadīth s. The paper shows that the influence of various theological currents, from neo-Muʿtazili to Saudi-Wahhābi, can be identified through the analysis of Indonesian Qur'an translations. It furthermore comes to the conclusion that it might be analytically meaningful to distinguish, first, between Qur'an translations and Qur'an commentaries, and second, between translations with a predominantly non-Muslim readership and those with a predominantly Muslim readership.